(untitled) (Mustansiria Dental Journal, 2005)
Recent studies have pointed the importance of Entamoeba gingivalis (E . gingivalis) as an active protozoa in periodontal pathology , its presence associated with the presence of pathological pockets , thus a clinical survey of E, gingivalis was conducted in patients with chronic periodontitis . A total of 240 specimens were taken Hom 48 patients (20 male and 28 female) , their age ranged from 38 up to 60 years old . A direct smearing technique of deepest periodontal pocket (> 4mm) with a sterile universal curettes to pickup the plaque material and to be placed in phosphate — buffered ` saline pl-7.4, then stained with Heidenhair hematoxilyne modified technique, studied under light microscope , the results shown 33.3% of our patients were positive . The occurrence of E. gingivalis appeared positively correlated with the pocket depth, 13.93% of 4-6mm pockets depth was positive, while in pockets of 7-8mm depth the percentage rises up to 38% .